Lack of interference with diagnostic testing for tuberculosis in goats experimentally exposed to Corynebacterium pseudotuberculosis. Issue 1 (July 2015) - Bezos, Javier; Casal, Carmen; Romero, Beatriz; Liandris, Emmanouil; Sánchez, Natalia; Vigo, Virginia; Domínguez, Lucas; de Juan, Lucía
Highlights Corynebacterium pseudotuberculosis might cross-react in the tuberculin test. Caprine caseous lymphadenitis does not interfere with diagnostic testing for tuberculosis. The single comparative intradermal tuberculin test is recommended to minimise false positives.